The method described by Czosnyka is particularly suitable for measuring CPPe in patients undergoing cerebral angiography - Yunyun Liang; Pei Mo; Yonghong Chen; Xinwu Liu; Lin Chen; Xiaomin Zhou; Zijing Wang; Junyi Fu; Longchang Xie (Frontiers in Surgery)
BackgroundThe primary objective of this study was to estimate the effective cerebral perfusion pressure (CPPe), critical closing pressure (CrCP), and resistance-area product (RAP) of the intravascular common carotid artery using three different methods. These estimates were then compared to the reference method of linear regression (LR).MethodsIn our previous study, we employed linear regression to evaluate the values of CrCP and RAP. To assess the consistency of results obtained from alternative assessment methods (CPPe, CrCP, and RAP) with the linear regression LR, we conducted a secondary analysis of the previously collected data. We estimated the CPPe, CrCP, and RAP of the intravascular common carotid artery using three different methods: Belford's method (mean/diastolic pressure), Czosnyka's method (systolic/diastolic pressure, CZO), and Schmidt's method (systolic/diastolic pressure, SCH), and compared these estimates with LR. CPPe is calculated as the difference between mean arterial pressure and CrCP. The primary outcome was the mean differences and biases between CPPe, CrCP, and RAP of intravascular common carotid artery, the secondary outcome was correlations and agreement among these various estimates of CPPe measurements.ResultsNineteen patients were included in this analysis. The median age was 53.5 ± 11.6 years, with 73.7% being men. There were no significant differences in CPPe, RAP and CrCP between the right common carotid artery (RCCA) and the left common carotid artery (LCCA) by using three different methods. Compared to the LR, the mean differences in CPPe and CrCP values were no significant for LCCA according to SCH, CZO and BEL method. But for RAP, the three methods are different in terms of mean differences compared with the LR. CPPe and CrCP revealed a small mean bias compared CPPCZO with CPPLR. Comparing CPPLR measurements with CPPBEL, the mean bias was higher with wider LoA. BEL and CZO showed a strong correlation with LR in Pearson correlation coefficients.ConclusionThe CPPe, CrCP, and RAP values obtained using the CZO calculation methods are comparable to those measured using the reference method. These findings may provide valuable insights for patients undergoing digital subtraction brain angiography, aiding in the determination of the most suitable approach for individualized blood pressure management.